YOUTH SUICIDES IN PAKISTAN - PRIORITIZING PREVENTATIVE STRATEGIES FOR A RISING PUBLIC HEALTH PROBLEM - Yousafzai, Abdul Wahab; Saman Yousuf, (Journal of Ayub Medical College Abbottabad, 2023)
Suicide is the third leading cause of death in adolescents worldwide. The World Health Organization (WHO) reports 90% of these suicides occur in lower-and-middle income countries (LMICs). Approximately a quarter of the population of Pakistan is under 19 years of age. Local research shows an alarming rise in suicides among youth and points to a complex set of biological, psychosocial and cultural factors. The time has come to shift our focus to planning culturally appropriate, indigenous preventative strategies engaging multiple sectors of the society to address this problem.